Development of a kinetic model for the hydrogenolysis of glycerol to propylene glycol by using Ni/FAP catalyst - Pandya, Harmitkumar N.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (ChemCatChem, 2026)
The rapid expansion of biodiesel production has led to an abundance of glycerol byproduct, necessitating efficient valorization into value added compounds such as 1,2-propylene glycol, (1,2-PG) and ethylene glycol (EG) by catalytic routes. In this study, a Ni/FAP catalyst was developed systematically and evaluated toward 1,2-PG. The wet impregnation method was used for the synthesis of Ni/FAP with varying nickel content on the FAP support. Comprehensive physiochemical characterization was performed using XRD, SEM-EDX, XPS, ICP-MS, CO chemisorption, and Nitrogen adsorption-desorption. Among the catalysts, 5% Ni/FAP provides optimal metal dispersion and accessible active sits, leading to moderate catalytic activity for glycerol hydrogenolysis reaction. To understand the reaction pathway and kinetics of the reaction, the Langmuir-Hinshelwood-Hougen-Watson (LHHW) model was developed. The activation energy of 81.5 kJ/mol estimates the kinetically controlled nature of the glycerol hydrogenolysis reaction.
Keywords: 1; 2-Propylene glycol; fluorapatite; Glycerol; Hydrogenolysis; LHHW; Nickel